A study on sexual functioning in adults with attention‐deficit/hyperactivity disorder. Issue 3 (11th February 2020) - Amani Jabalkandi, Samaneh; Raisi, Firoozeh; Shahrivar, Zahra; Mohammadi, Abolfazl; Meysamie, Alipasha; Firoozikhojastefar, Reihaneh; Irani, Fatemeh
Abstract: Purpose: Sexual dysfunction has been ignored in adults with attention‐deficit hyperactivity disorder (A‐ADHD). This study examined sexual function in adults with ADHD compared to a healthy control group. Design and Methods: The experimental group (N = 63, mean age = 31.11 ± 4.29, females = 31) were recruited among referrals with ADHD to an outpatient A‐ADHD clinic. The DIVA‐2 (Diagnostic Interview for ADHD in adults) and the schedule for affective disorders and schizophrenia (SADS) were used to assess for A‐ADHD and comorbid psychiatric disorders, respectively. The healthy groups (N = 66, mean age = 31.37 ± 4.30, females = 31) were demographically matched and had no psychiatric disorders based on the Conners' Adult ADHD Rating Scales—Self Report, Short Version and SADS. Sexual functions were evaluated using the Female Sexual Function Index (FSFI) for females and International Index of Erectile Function (IIEF) for males. Findings: Females with ADHD compared to the control group showed significantly ( P  < .001) poorer scores in all FSFI domains (desire, arousal, orgasm, satisfaction, pain, and lubrication). The IIEF mean scores in the males with A‐ADHD were lower ( P  = .00) than their counterparts for all the subscales including orgasm, erectile function, intercourse satisfaction, and overall satisfaction, except for the desire ( P  = .75). The orgasmic function had a significant negative correlation with Conners Adult ADHD Rating Scale—Self Report: Short total scores in males (r = −.48) and females (r = −.40). Practice Implications: This study provides preliminary information on greater difficulties with sexual function in adults with ADHD. Assessment of sexual function in referrals with A‐ADHD is suggested.